Autonomy of health care facilities: it is more an ideal than an institutional reality - Gloria Molina M; Martha Liliana Hernández; César Augusto Carrioni (Universidad de Antioquia, 2007)
The issue of hospital autonomy has aroused considerable international interest since the mid-1990's, especially with regard to its linkage to governmental decentralization processes and reform of the health ﬁeld. Non-proﬁt hospitals have increasingly been obliged to become more autonomous as they compete for funding with private institutions. Objective: to understand how autonomy expresses itself through key management processes in non-proﬁt and for-proﬁt hospitals both in Medellín, the second largest city of Colombia, and its metropolitan area. Different institutional factors-political, administrative and economic-inﬂuencing autonomy are examined. Methods: a grounded theory method was used, consisting of semi-structured interviews with managers in six hospitals. Results: ﬁndings suggest that autonomy is perceived more as an ideal to aspire to, which would enable the hospital management to make free decisions, providing services in a manner that ensures ﬁnancial sustainability. In practical terms, however, the degree of administrative and ﬁnancial autonomy is circumscribed by both internal organizational factors associated with hospitals characteristics and external factors associated with institutional environment.